A case study of the 2023 highly pathogenic avian influenza (HPAI) outbreak in tern (Sternidae) colonies on the east coast of the Republic of Ireland - Burke, Brian; Adcock, Tara; Boland, Helen; Büche, Birgitta; Fitzgerald, Micheál; Johnson, Giles C.; Monaghan, Jason; Murray, Tony; Stubbings, Edward; Newton, Stephen (Bird study, 2024)
HPAI H5N1 had a significant impact on breeding Common Terns Sterna hirundo, Arctic Terns Sterna paradisaea and Roseate Terns Sterna dougallii on the east coast of the Republic of Ireland (ROI) in 2023, with a lesser impact on Sandwich Terns Thalasseus sandvicensis and only two cases among Little Terns Sternula albifrons. To document the outbreak of HPAI H5N1 in the tern colonies on the east coast of ROI during the 2023 breeding season. Precautions were taken from the start of the breeding season, including personal protective equipment (PPE) and safe operating procedures. Regular meetings were held between BirdWatch Ireland and the National Parks and Wildlife Service ( NPWS) to respond to the emerging situation. Once HPAI was confirmed in a colony, all ringing and nest visits were stopped. Carcass removal was carried out at all affected colonies and most carcasses were incinerated. Common Terns suffered the highest mortality across all colonies in 2023, with smaller but notable numbers of dead Roseate Terns and Arctic Terns, but very few Sandwich Terns and only two Little Tern deaths were attributed to HPAI. Regular meetings between relevant organizations were invaluable in preparing for outbreaks and ensuring an adaptive approach as the situation changed over time and between colonies. There was no way of knowing if the actions taken were effective, as the pattern of virus spread between species and sites remains poorly understood. Future clarity over the role of various state agencies and other relevant bodies in responding to HPAI in wild birds, greater sharing of real-time information, and pre-arranged agreements to ensure rapid testing and disposal of carcasses, would be useful to ensure an effective response to future outbreaks.